PHYSICAL ACTIVITY AS A METHOD OF RECOVERY OF PSTU STUDENTS IN CONDITIONS AFTER STRESS SITUATIONS - Зюзь, Владимир; Балухтина, Валентина (SWorldJournal, 2023)
The article is devoted to the organization of the formation of positive skills to overcome stress, which is relevant for students who do not yet have sufficient experience in dealing with stress and crises.As a specific stressful situation, this paper co